Clinical value of oral fluid chemokines in chronic periodontitis - V. V. Bazarnyi; Yu. V. Mandra; L. G. Polushina; A. Yu. Maksimova; E. N. Svetlakova (Медицинская иммунология)
Activation of cytokine network is one of the key mechanisms in immunopathogenesis of chronic periodontitis (CP), a common dental disease. Therefore, the study of the proteomic (including cytokine) profile of saliva is not coincidentally considered among global research areas in periodontology. However, the existing data on the contents of cytokines / chemokines in oral fluid (OF) in CP are contradictory. This ambiguity of the results can be associated both with a variety of methodological approaches to the cytokine determination, and with different severity of CP in the studied cohorts of patients. Moreover, recent systematic reviews and meta-analyses show that clinical value of chemokines in CP is also not yet determined thus indicating a need for future research in this area.The aim of this study was to assess clinical and diagnostic value of some chemokines from oral fluid in chronic mild periodontitis. The work was based on a study of 18 patients diagnosed with mild chronic periodontitis (MCD-10 K05.3) and 12 practically healthy volunteers with relatively intact periodontal tissue. The diagnosis was based on standard clinical and radiological criteria. In all cases the levels of 8 chemokines were determined using multiparametric fluorescence analysis with magnetic microspheres (xMAP technology, Luminex 200, USA). Statistical analysis was carried out by methods of non-parametric statistics. To determine the predictive value of the test, ROC analysis was performed.It has been shown that CP is accompanied by increased levels of CXCL1 (5.5-fold), CXCL8 (8.1-fold), CXCL12 (3.5-fold), CCL2 (2.7-fold). At the same time, the level of other chemokines did not change significantly. There was a lack of correlations between individual parameters in the group of patients with CP, in contrast to the control group, thus, probably reflecting disturbed mechanisms of “balance” regulation of chemokines. By means of ROC analysis, highly sensitive biomarkers of chronic mild periodontitis were identified. The diagnostic sensitivity and diagnostic specificity were for CXCL1 (91 and 75%, respectively), CXCL8 and CXCL12 (95 and 75%), CCL2 (82 and 75%). The data obtained indicate that the salivary chemokines CXCL1, CXCL8, CXCL10, CXCL12, CCL2 can be considered potential biomarkers of mild chronic periodontitis.